2020
DOI: 10.21660/2020.67.5807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Change on Milk Yield and Milk Composition in Thai Crossbred Holstein Cows

Abstract: The purpose of this research was to study effects of climate changes on milk yield and milk composition of Holstein crossbred . This study uses data recording total milk production per farm each day and milk composition (from 2013-2017): fat percentage (% Fat), protein percentage (% Pro), solid not fat percentage (% SNF) and total solid percentage (% TS) from 79 farmers in Mahasarakham Province, Thailand. The temperature and humidity data were obtained from records of meteorological center. Using temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The effect of climate variables on the cattle milk production was represented by Table 1. The regression analysis indicated that minimum temperature had shown a positively significant relationship with indigenous cow milk production at 10% level of significance, whereas; maximum temperature and relative humidity had expressed a positively non-significant relationship [11]. The 1 0 C increase in annual minimum temperature increased the indigenous cow milk production by 3.3% for the present study.…”
Section: Effect Of Climate Change On Cattle Milk Productionmentioning
confidence: 45%
“…The effect of climate variables on the cattle milk production was represented by Table 1. The regression analysis indicated that minimum temperature had shown a positively significant relationship with indigenous cow milk production at 10% level of significance, whereas; maximum temperature and relative humidity had expressed a positively non-significant relationship [11]. The 1 0 C increase in annual minimum temperature increased the indigenous cow milk production by 3.3% for the present study.…”
Section: Effect Of Climate Change On Cattle Milk Productionmentioning
confidence: 45%
“…Future research focusing on the effect of these parameters on colostrum metabolome, especially in tropical dairy farming environments, could be of great interest. Although variations in milk composition associated with the origin of the farm (many factors involved) and sampling period (milking time, seasons, and climate) have been well acknowledged (Promket et al, 2020;Puppel et al, 2019), available data of these effects on the overall metabolite profile or molecular fingerprint of colostrum is rather limited. This information could help to suggest directions for improving dairy management to achieve the desired colostrum quality.…”
Section: Tasj-32598_revised By Authormentioning
confidence: 99%